Multi-objective optimisation of hydro-pneumatic suspension with gas–oil emulsion for heavy-duty vehicles. Issue 7 (2nd July 2020) - Kwon, Kihan; Seo, Minsik; Kim, Hansu; Lee, Tae Hee; Lee, Jongseok; Min, Seungjae
Abstract : In the development of heavy-duty vehicles, the design of hydro-pneumatic suspension (HPS) is important for improving various aspects of vehicle performance, such as comfort and stability. An HPS with gas–oil emulsion is advantageous with respect to cost and design compared to that with a separated chamber, because it shares a chamber with gas and oil. This paper presents an optimisation procedure for obtaining the optimal design of HPS with gas–oil emulsion for heavy-duty vehicles. The HPS model is developed from a mathematical analysis of the gas–oil emulsion, and a parameter study is performed to confirm the design sensitivity of the spring and damping characteristics. A full vehicle model with HPS is constructed to analyse the vehicle performance. The necessity of this vehicle model is shown by comparing its results with those of a simplified vehicle model. To alleviate the problem of excessive computational effort caused using the full vehicle model, surrogate models with respect to performance are developed for the design optimisation of HPS. By performing a multi-objective optimisation of the HPS design, a Pareto front considering the contradiction between the comfort and stability of the performances is obtained.